Remineralizing effect of commercial fluoride varnishes on artificial enamel lesions - Fernanda Alvarez de Godoi; Natália Russo Carlos; Enrico Coser Bridi; Flávia Lucisano Botelho do Amaral; Fabiana Mantovani Gomes França; Cecilia Pedroso Turssi; Kamila Rosamilia Kantovitz; Roberta Tarkany Basting
Abstract: The aim of this study was to evaluate soluble and insoluble fluoride concentrations in commercial varnishes, and their remineralization effect on artificial caries enamel lesions using surface and cross-sectional microhardness evaluations. Forty bovine enamel blocks were separated into four groups (n=10): control (no treatment), Enamelast (Ultradent Products), Duraphat (Colgate-Palmolive) and Clinpro White Varnish (3M ESPE). Surface enamel microhardness evaluations were obtained, artificial enamel caries lesions were developed by dynamic pH-cycling, and the varnishes were then applied every 6 days, after which the enamel blocks were submitted to dynamic remineralization by pH cycles. After removal of the varnishes, the enamel surfaces were reassessed for microhardness. The blocks were sectioned longitudinally, and cross-sectional microhardness measurements were performed at different surface depths (up to 300 μm depth). Polarized light microscopy images (PLMI) were made to analyze subsurface caries lesions. The fluoride concentration in whole (soluble and insoluble fluoride) and centrifuged (soluble fluoride) varnishes was determined using an extraction method with acetone. The data were analyzed to evaluate the surface microhardness, making adjustments for generalized linear models. There was a significant decrease in enamel surface microhardness after performing all the treatments (p<0.0001). Enamelast and Duraphat showed significantly higher enamel microhardness values than the control and the Clinpro groups (p = 0.0002). Microhardness loss percentage was significantly lower for Enamelast (p = 0.071; One-way ANOVA). PLMI showed that subsurface caries lesions were not remineralized with the varnish treatments. No significant differences in the in-depth microhardness levels (p = 0.7536; ANOVA) were observed among the treatments. Enamelast presented higher soluble and insoluble fluoride concentrations than the other varnishes (p < 0.0001; Kruskal-Wallis and Dunn tests). Enamelast and Duraphat varnishes promoted enamel surface remineralization, but no varnish remineralized the subsurface lesion body. Although insoluble and soluble fluoride concentration values did not correspond to those declared by the manufacturer, Enamelast presented higher fluoride concentration than the others.